Strengthening Literacy of ABACAGA Method at PNF PKBM KRI Embassy Malaysia - Faridatus Sholiha; Faradila Aini; Mohamad Mahsun; Haidar Idris; Saiful Bakhri; Zainul Arifin; Ahmad Ihwanul Muttaqin; Ihya’ Ulumudin; Muhammad Masyhuri; Syamsul Arifin; Muhammad Abdul Halim Sidiq (IJECS: Indonesian Journal of Empowerment and Community Services, 2025)
ABSTRACT Some Indonesian students aged 10–12 at the Indonesian Embassy in Malaysia's PNF Learning Center (PKBM PNF) still demonstrate low basic literacy skills. This condition is related to family backgrounds that do not have clear legal status due to unregistered marriages and the lack of valid citizenship documents. In addition, parental involvement in accompanying children's learning process at home is relatively low due to the demands of full-time work. This study aims to accompany and improve basic literacy skills through the ABACAGA Guidebook and contextual fiqh materials. The population in this study were PMI elementary school children in grades 1 and 2 with a sample of 20 students. This study used a qualitative empirical method with a participatory approach. Data were obtained through observation, interviews, pre-tests and post-tests, and direct documentation in the field. The conclusion from the results of this mentoring was able to improve basic literacy skills, strengthen children's learning habits, and introduce basic fiqh understanding such as ablution, prayer, and short readings. Each child we support shows varying levels of progress, proving that all children excel in their own talents, and with the right approach, they can develop optimally, even with limitations.   Keywords: literacy, abacaga method, Islamic jurisprudence